THE EVIDENCE OF ASTRONOMY AND TECHNICAL CHRONOLOGY FOR THE DATE OF THE CRUCIFIXION1 - Fotheringham, J. K. (The journal of theological studies, 1934)
J. K. FOTHERINGHAM; THE EVIDENCE OF ASTRONOMY AND TECHNICAL CHRONOLOGY FOR THE DATE OF THE CRUCIFIXION1, The Journal of Theological Studies, Volume os-XXXV, Iss